Electrochemical Impedance Spectroscopy Evaluation of Organic Coating on Mild Steel - Zainoldin, Zailelah; Bahron, Hadariah; Kamal Harun, Mohamad; Athirah Dzolin, Syaidah (International Journal of Engineering and Technology, 2018)
Electro-oxidation of 4-hydroxybenzalaniline in alkaline solution on mild steel surface was successfully carried out using cyclic voltammetric technique. Results demonstrated that brownish colour appeared on the mild steel surface after the cycle of voltammetric study. The presence of film was confirmed by the EIS measurement whereas the Nyquist plots obtained from EIS measurements were fitted with suitable electrical equivalent circuit. The coated mild steel exhibit better polarization resistance than uncoated mild steel.Â Â